Billi’s Anxiety and Defense in The Farewell Film by Lulu Wang - Fadillah, Alif; Zamruddin, Mardliya Pratiwi; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2024)
This research analyzes anxiety and defense mechanism by Sigmund Freud in The Farewell Film. The objective of this study is to describe how anxiety and defense mechanism portrayed through Wang as the main character in the film. This research uses qualitative design. The data are dialogues and scenes that are related to anxiety and defense mechanism. The data are analyzed by using Freud’s theory and the process of data analysis is using Miles and Huberman’s theory. Based on the result of this study, the researchers make two points. Two theories are presented by the main character. Anxiety was displayed by the character. Billi's grandmother, who was diagnosed with cancer, could not live much longer. Defense mechanisms include regression, rationalization, sublimation, and repression. Due to her anxiety, Billi applied various defenses attitudes unconsciously. Unconsciously, Billi suppresses his discomfort in many ways, including having fun, thinking rationally, and carrying out useful social activities. The second reason is that Billi uses the defenses to maintain her relationship with her family as well as to counter anxiety. As a result, Billi suppressed her id in order to maintain good relations with her family by suppressing her personal interests.Keywords: Anxiety, Defense mechanism, Psychoanalysis